Komunikasi Pemasaran dalam Mempromosikan Aplikasi Nujek - Ihda 'Ainaya Zulaikha; Nuryanti Nuryanti; S. Bekti Istiyanto (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The process of developing the Nujek application is carried out by PT Tekno Karya Nusa (Nujek) in Banyumas by promoting it through social media using either Facebook, Instagram or Tiktok social media. The results of this study are to see the implementation of Nujek Banyumas social media content as a marketing communication strategy in promoting the Nujek application. There are several indicators of social media, such as Facebook has a dominance to interact with audiences, Instagram social media has the characteristics of visualizing content to communicate, and Tiktok social media is used to disseminate promotions regarding Nujek products or applications. The purpose of this study is to determine the implementation of social content Nujek Banyumas media in conducting promotions as a form of marketing communication strategy.